o ensino de leitura na escola: um olhar sobre as concepções de professores do 1º ciclo do ensino fundamental de uma escola municipal de Bauru - SP - Martins, Ana Suellen [UNESP] (2010)
This research is being read, thus rendering text on the pole of understanding, as a practice effective dialogue and therefore responsive through which the reader, author, text and context interact. To this end, the reader must turn their knowledge systems and relate them to the linguistic materiality. Thus, aimed to investigate whether the teaching of reading in the early years of elementary school literacy builds skills related to this cultural practice and its relationship to the conceptions of classroom teachers of reading, as well as the teaching and learning methodologies practiced in class classroom. Therefore, I base this research on the theoretical basis of linguistic studies and expository sociointeractionist redefine that, among other things, the concepts of language, genre and text. As for the methodological framework, this study followed the methodology of literature research and fieldwork. The fieldwork took place from the perspective of observing the pedagogical practice of teaching reading, in order to investigate how the educational activities are conducted in a reading room for the third year of elementary school, part of the municipal education Bauru- SP. Were used as instruments of data collection the questionnaire given to school teachers and the school studied the direct observation of teaching practice of one of these professionals. The results of data analysis indicate that the teachers surveyed know key content for teaching reading, as well as renovations of the theoretical and methodological studies of reading, with the consequence that the practices of reading done in the classroom limit the role of student as a reader and does not guarantee the formation of the reader